# If f(x)=l5-3xl, then f(2)=?

A)f(-2)

B)f(-1)

C)f(1)

D)f(4/3)

E)f(7/3)

How come the answer is D?

Thank u :)

### 5 Answers

- ?Lv 74 weeks agoFavorite Answer
f(x) = l5-3x| ⇒

..........f(2) = |5 - 3(2)|

..........f(2) = |5 - 6|

..........f(2) = |-1|

..........f(2) = 1

// Check to see which option equals f(2)

A) f(-2) = |5+6| = 11

B) f(-1) = |5+3| = 8

C) f(1) = |5-3| = 3

D) f(4/3) = |5 - 3(4/3)| = 1........................ANS

E) f(7/3) = |5 - 3(7/3)| = -2

- KrishnamurthyLv 74 weeks ago
If f(x) = |5 - 3x|, then f(2) = 1

Answer choice:

C) f(1)

The answer is not D.

- PuzzlingLv 74 weeks ago
Because it is an absolute value function, we know that the positive version and the negative version will give the same result.

f(2) = |5 - 3(2)| = |5 - 6| = |-1| = 1

But we also know that if the part in the absolute value is *1* we'll get the same answer.

5 - 3x = 1

-3x = -4

x = -4/-3

x = 4/3

Summary:

f(4/3) = 1

f(2) = 1

Answer:D) f(4/3)

- How do you think about the answers? You can sign in to vote the answer.
- RaymondLv 74 weeks ago
f(x) = | 5 - 3x |

f(2) simply means: use the operation on the right of the equal sign, and use the value 2 wherever you see "x".

The operation on the right (in this case) asks for an "absolute value", meaning the distance from zero.

With ordinary numbers, it simply means the value without the sign.

The symbol is unofficially called "the pipes". Whatever total value is inside "the pipes" loses its negative sign.

|+7| = 7 because the distance from 0 to +7 is 7 units.

|-7| = 7 because the distance from 0 to -7 is also 7 units

(distances are always positive values - as opposed to "displacement" that may take direction into account)

f(2) = | 5 - 3*2 | = | 5 - 6 | = | -1 | = 1

The value inside the pipes is -1, and its distance from 0 is... 1.

What other way can we get a distance of 1?

By having the value inside "the pipes" being +1

This can be done with using |5 - 4| (instead of |5-6|)

To get -4 out of -3x, you need x = 4/3

Therefore f(4/3) = | 5 - 3(4/3) | = | 5 - 4 | = |+1| = 1

which is equal to f(2)